Sustainable supplier selection criteria classification for Indian iron and steel industry: a fuzzy modified Kano model approach - Naveen Jain; A. R. Singh (International Journal of Sustainable Engineering, 2020)
The aim of this work is to provide a systematic approach for sustainability criteria clustering into different useful categories. For this purpose, a methodology has been proposed with the following three steps. (i) A comprehensive set of the sustainability criteria in economic, environmental and social dimension has been extracted from the literature and have been customised for the iron and steel industry. (ii) A fuzzy Kano methodology has been used to classify these sustainability criteria into useful Kano cluster like must-be, one-dimensional, and attractive cluster (iii) further, must-be and attractive criteria derived from the second step were further sub-classified into three categories using Type IV Kano model. All steps have been examined in the iron and steel industry of India and findings indicate that quality and delivery criteria are classified as high must be criteria in the economic realm. Further, environmental and energy management system in the environmental dimension and social responsibility and right of stakeholders criteria in the social dimension are classified as high must be criteria. Prioritising must be and attractive criteria enable decision makers of other industries to select the appropriate criteria to adopt sustainability.